MONITORING EVALUATION OF URBANOZEMES OF SMALL CITIES OF THE BRYANSK REGION - Elena Vasylyevna Borzdyko; Marina Vasilievna Avramenko; Igor Vladimirovich Moskalenko; Lydia Nikolaevna Anishchenko (Siberian Journal of Life Sciences and Agriculture, 2019)
For the first time, a monitoring base has been created for the Bryansk region (Non-Black Earth Region of the Russian Federation) on the ecological, chemical and algological indicators of soils in small cities, which differ in population and the development of industrial production. Routing methods, methods of chemical and algological soil research were used. The general condition of urban soils was evaluated by the Zс index.